2011
DOI: 10.1515/rjnamm.2011.002
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of surface waves generated by an underwater landslide moving over an uneven slope

Abstract: This paper is focused on the study of the effect of an underwater slope unevenness on the wave mode characteristics caused by the motion of a landslide over this slope. Using the simplest model representation of a landslide in the form of a rigid body, the authors consider two model reliefs, taking to some extent into account the peculiarities of the Mediterranean coast of Israel. The simulation of wave processes is performed within the framework of the equations of the shallow water theory. The results of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
(17 reference statements)
0
6
0
1
Order By: Relevance
“…However, strictly speaking the employed empirical models are valid only for an absolutely rigid landslide sliding down a constant slope. Subsequent numerical simulations showed that the bottom shape influences quite substantially the generated wave field [13]. Consequently, for realistic modelling of real world cases one needs to take into account the actual bathymetry [103] and even possible deformations of the landslide during its motion [102].…”
Section: Wave Generation By An Underwater Landslidementioning
confidence: 99%
“…However, strictly speaking the employed empirical models are valid only for an absolutely rigid landslide sliding down a constant slope. Subsequent numerical simulations showed that the bottom shape influences quite substantially the generated wave field [13]. Consequently, for realistic modelling of real world cases one needs to take into account the actual bathymetry [103] and even possible deformations of the landslide during its motion [102].…”
Section: Wave Generation By An Underwater Landslidementioning
confidence: 99%
“…T (x) corresponds to the leading elevation N -wave solution (LEN), while the second function η (2) T (x) is a typical leading depression N -wave (LDN). The results of optimization procedures are shown on Figures 5 and 6.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Non-hysrostatic effects lead the appearance of linear dispersive terms in the governing equations. The problem of landslide generated waves has been addressed in the fully nonlinear shallow water framework [65,15,56,8]. Nevertheless, several authors obtained recently interesting results even in the linear [53,54] or nonlinear [27,18,7] hydrostatic models.…”
Section: The Boussinesq Modelmentioning
confidence: 99%